Revisiting local structural changes in GeO2 glass at high pressure. (20th October 2017) - Dong, Juncai; Yao, Hurong; Guo, Zhiying; Jia, Quanjie; Wang, Yan; An, Pengfei; Gong, Yu; Liang, Yaxiang; Chen, Dongliang
Abstract: Despite the great importance in fundamental and industrial fields, understanding structural changes for pressure-induced polyamorphism in network-forming glasses remains a formidable challenge. Here, we revisited the local structural transformations in GeO2 glass up to 54 GPa using x-ray absorption fine structure (XAFS) spectroscopy via a combination diamond anvil cell and polycapillary half-lens. Three polyamorphic transitions can be clearly identified by XAFS structure refinement. First, a progressive increase of the nearest Ge–O distance and bond disorder to a maximum at ~5–16 GPa, in the same pressure region of previously observed tetrahedral-octahedral transformation. Second, a marked decrease of the nearest Ge–O distance at ~16–22.6 GPa but a slight increase at ~22.6–32.7 GPa, with a concomitant decrease of bond disorder. This stage can be related to a second-order-like transition from less dense to dense octahedral glass. Third, another decrease in the nearest Ge–O distance at ~32.7–41.4 GPa but a slight increase up to 54 GPa, synchronized with a gradual increase of bond disorder. This stage provides strong evidence for ultrahigh-pressure polyamorphism with coordination number  >6. Furthermore, cooperative modification is observed in more distant shells. Those results provide a unified local structural picture for elucidating the polyamorphic transitions and densification process in GeO2 glass.